PENGARUH PROGRAM FULL DAY SCHOOL TERADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MADRASAH IBTIDAIYAH (MI) DARUSSALAM LUBUKLINGGAU - Joni Helandri (Edification Journal : Pendidikan Agama Islam, 2019)
Darussalam Islamic Primary School is one of the schools which applied the Full Day School, the researchers want to find out correlation on the Full Day School toward the Fifth Grade Students’ achievement. Qualitative and Survey approaches are used in this research. Researchers used Questionnaires, Document, analyz data Descriptive and Inferential Statistics through Normality test, Linear Regression and Correlation analysis. the result, it was found out that (1) the “application”Moderate level”, 56 students or 100%,(2) the“students’ achievement” on the Fiqh“Moderate Level” 56 students or 100%, and (3) the correlation” of the Full Day School program DF=N-Nr, N=56 Nr=2, that is 56-2=54, r table 5% significant level 0.266 and significant level 1% 0.345. r= 0.788 higher than r-table, 5% level or 1% level or 0.266<0.509>0.345. Ha is accepted and Ho is rejected. there significant effect of Full Day Program toward the Fifth Grade Students’ Achievement on the “Fiqh”at MI Darussalam.